Validity of a swimming snorkel for metabolic testing - Rodriguez, F. A.; Keskinen, K. L.; Kusch, M.; Hoffmann, U. (International Journal of Sports Medicine, 2008)
Two models of a swimming snorkel connected to a portable metabolic cart (Cosmed K4 b2, Rome, Italy) were assessed using a gas exchange simulation system. Four standardized testing protocols were designed to mimic different swimming conditions and were performed similarly in three conditions so that both snorkels could be compared to measured values obtained by connecting the simulator directly with the gas analyzer. Simulated and measured values were highly correlated (R2 = 0.891 to 0.998) and in good agreement, with only a small overestimation of expiratory tidal volume (4 %, p = 0.005), not large enough to significantly affect the accuracy of ventilation or gas exchange parameters. Values measured using both swimming snorkels also highly correlated with simulated values, particularly for the ventilatory and primary gas exchange variables (R2 = 0.996 and 0.998 in both models for V·O2 and V·CO2, respectively). A moderate overestimation of FEO2 was observed in both models (2.65 % and 2.48 % relative, p = 0.03) and attributed to minimal mixing of inspiratory and expiratory gases, although not affecting V·O2 measurements. We conclude that both snorkels are valid devices for measuring pulmonary breath-by-breath gas exchange parameters in connection with the K4 b2 across a wide physiological range.